Chub mackerel as potential lipid-based functional food - Eleonora Valentia Sode Muda; Adinda Aulia Rahma; Brian Jonathan; Jefferson Nathanael Chandra; Jessica Michelle Liony; Muhammad Fajar Kuntadi; Junaida Astina (Universitas Bio Scientia Internasional Indonesia, 2025)
Functional foods have gained a lot of attention as people become more aware of the importance of human nutrition. Chub mackerel is classified as one of the functional foods due to being rich in omega-3 fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) that are associated with various health benefits, including anti-inflammatory properties, cardiovascular health support, and cognitive function enhancement. Additionally, chub mackerel also contains high protein, vitamin, and mineral content that contribute to muscle growth, immune system support, and cognitive function improvement. Research has indicated the safety and efficacy of consuming omega-3 from chub mackerel, particularly among vulnerable populations like pregnant women and children. Various processing techniques have been applied to chub mackerel to enhance its quality as a functional food, including roasting and frying. However, non-thermal processing may better preserve the nutritional compositions, mitigating nutrient losses during processing. The future outlook for chub mackerel as a functional food includes further research into alternative cooking methods to preserve omega-3 content and the implementation of regulatory measures and industry collaborations to promote its utilization as a functional food, particularly in regions like Indonesia where it is abundant and affordable. Overall, chub mackerel shows promise as a lipid-based functional food with significant potential for improving public health and addressing the rising prevalence of non-communicable diseases.